Perancangan Interior Pusat Terapi Anak Autis Dan Indigo berdasar Pendekatan Psikologi Interior di Surabaya - Wijayanto, Anastasia Vera (Intra, 2013)
Autism and indigo is one of unusual phenomena that happening to some childs. In the case of interior design with special needs-like autism and indigo children-, we need a spesific design that fulfill needs, efficient in doing therapy and self-development. Basicly from that reasons, the functions of interior design not only for fulfill functions and aesthetics, but also cares about societyâs problems, especially for special needs userâs.Â Â Â Â Â Â Â Â Â Â Â  This design based on approach of interior psychology and psychological effects to the childâs psychologic. Facilities include theraphy facility, academics facility, counceling facility, canteen, and extraculiculair facility. Design concepts based on the needs ofÂ  childâs development and for optimize the process of therapy, counceling, and academics for autism and indigo childs.